You actually are interpreting the arrows quasi-correctly.
Step 1: 3^3
Step 2: 3^^3 = 3^27 = 7.6T
Step 3: 3^(3^^3) = 3^3^3^3 = 3^^4
Step 4: 3^(3^^4) = 3^^5
The tricky part to wrap your head around is the addition of a third arrow.
New Step 3: 3^^^3 = 3^^(7.6T) which means repeating your original version of Steps 4, 5, 6, etc. all the way to Step 7.6T! Then you would have to add yet *another* arrow, which means you have to take the result of that Step #7.6T and continue repeating your steps to reach *that* step number. Then, FINALLY, you would have G1.
Brain broken yet?